ANALYSIS OF CONSTRUCTIVE FEATURES OF ABSORBERS - Lyakh, M. M.; Mykhaylyuk, V. V.; Protsyuk, V. R.; Deineha, R. O.; Petrynka, A. V.; Fafley, O. YA. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2023)
The production of cement mixtures is accompanied by significant emissions of harmful substances: the formation of nitrogen oxides, dust emissions from furnaces, clinker coolers and mills for grinding raw materials, water vapor, sulfur dioxide, oxide and carbon dioxide, etc. These emissions cause significant damage to the environment. Despite modern technologies and equipment used to eliminate the negative impact of cement production on the environment, it is impossible to completely eliminate it. Therefore, the capture, storage and further use of harmful elements as raw materials in the flue gases of cement enterprises is an important task today. The paper analyzes the main sources of harmful emissions during cement production and existing ways of reducing them. Emphasis is placed on the application of the absorption method and the mechanisms of its use. A critical analysis of the existing types of plate and nozzle absorbers was carried out, the designs of industrial mass exchange nozzles were analyzed, which ensure the intensification of the mass exchange process, the reduction of hydraulic resistance, the reduction of energy consumption, etc. When designing for the further operation of absorbers, it is important to evaluate their efficiency, which includes the characteristics of process intensity and hydraulic resistance. The selection of an absorber for each specific task should be carried out as a result of technical and economic calculations carried out for several competing types. At the same time, it is necessary to take into account the ease of manufacture, consumption of metal and other materials, cost, ease of use, etc.